Pertumbuhan Ekonomi dan Konsumsi Energi: Pengaruhnya Terhadap 3 Negara Mayoritas Muslim Dengan Emisi Karbon Tertinggi - Landapa, Sonia Ista Iswari (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to analyze the influence of economic growth and energy consumption on the carbon emissions of the three Muslim-majority countries with the highest carbon emissions in the world. The data used is 1993-2022. The research locations are Indonesia, Saudi Arabia and Iran. The analysis method of this study is multiple linear regression analysis of panel data. The results of economic growth research have a negative and significant effect on carbon emissions, while energy consumption does not have a significant effect on carbon emissions.